2012
DOI: 10.2754/avb201281010015
|View full text |Cite
|
Sign up to set email alerts
|

Viral infections in queen bees (Apis mellifera carnica) from rearing apiaries

Abstract: Viral infection could have an impact on the success of queen rearing and a potential effect on reduced queen quality. Newly mated honey bee (Apis mellifera carnica) queens were collected from mating nuclei in queen rearing operations in Slovenia. Altogether, 81 queens were sampled from 27 rearing apiaries in 2006 and 72 queens from 24 apiaries in 2008. Queens were analysed for the presence of four viruses: acute bee paralysis virus (ABPV), black queen cell virus (BQCV), sacbrood virus (SBV) and deformed wing v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…It was found that mating can transmit viral disease; mated queens are older than virgin queens, which results in a higher probability of infection from workers or as a result of vertical virus transmission (Gauthier et al, 2011). In our previous research, we noted that DWV was found in normally-developed, laying queens despite Varroa control (Gregorc and Bakony, 2012). The results of this survey will help queen breeders and extension specialists improve rearing technologies and queen mating conditions that are essential for certifying queens for commercial sale.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that mating can transmit viral disease; mated queens are older than virgin queens, which results in a higher probability of infection from workers or as a result of vertical virus transmission (Gauthier et al, 2011). In our previous research, we noted that DWV was found in normally-developed, laying queens despite Varroa control (Gregorc and Bakony, 2012). The results of this survey will help queen breeders and extension specialists improve rearing technologies and queen mating conditions that are essential for certifying queens for commercial sale.…”
Section: Discussionmentioning
confidence: 99%
“…Viral RNA was isolated using a QIAamp Viral RNA Mini Kit (Qiagen, Germany) according to the instructions. Altogether, 232 queens were examined (81 queens from the year 2006, 72 from 2008, and 69 queens from 2010) for the presence of ABPV, BQCV, DWV, and SBV, as cited by Gregorc and Bakony (2012). Viral RNA was reverse transcribed and amplified by a continuous RT-PCR method with the One Step RT-PCR kit (QIAGEN, Germany), according to the manufacturer's instructions.…”
mentioning
confidence: 99%
“…DWV is a known cause of colony mortality in association with its vector, Varroa destructor [73], and it also serves as a convenient study model because it readily infects all developmental stages and castes [74]. DWV venereal transmission was demonstrated through instrumental insemination [52,53] and in free-flying mated queens [75,76]. High DWV titer detected from endophalli collected from captured drones from the drone congregation areas or from queens returning from their mating flights support that DWV venereal transmission can occur during natural mating [35,77].…”
Section: Viral Transmission Modes To Honey Bee Queensmentioning
confidence: 99%
“…Consequently, little is known about how virus infections affect the behavior, physiology, reproduction, and longevity of queens. Numerous viruses (DWV, SBV, CBPV, ABPV, KBV, and IAPV) have been detected from heathy looking queens, demonstrating that infection can occur either by single or multiple viruses in a queen [75,76,78,92]. Viruses infect different parts of the queen's body, including the head, thorax, ovaries, spermatheca, and fat body [56,59,79,93].…”
Section: Direct Health Impacts Of Viruses On Queensmentioning
confidence: 99%
See 1 more Smart Citation